(untitled) (Global Journal of Human-Social Science, 2012)
At a time like this when the quest for good governance is a global desire of people of different land and clime most especially in the African region the discourse of good governance and progress at the grassroots level in Nigeria could not have been more apposite This paper examines the concepts of governance development progress and corruption within the Nigerian socio-economic and political milieu with the view to showing assessing the governance status and the various efforts of the government in combating the scourge The position of Claude Ake is perfectly supported in this paper